Living in the present: Women’s everyday experiences of living with rheumatoid arthritis - Barns, Angela; Svanholm, F.; Kjellberg, A.; Thyberg, I.; Falkmer, Torbjorn (SAGE Publications, 2015)
This article presents the findings from a qualitative research project exploring eight women’s experiences of living with rheumatoid arthritis (RA). Through semistructured interviews, the women provided insights into the physical, emotional, and social impacts of RA and the “work” involved in negotiating its influence in the everyday life. In narrating their experiences of adapting to RA, the women express a common desire for “normalcy,” to return to a time and space before the disruption of RA. The women’s accounts also emphasized the interrelatedness between bodily experience and constructions of self, highlighting the corporeal nature of RA and the constant shaping and reshaping of personal meanings and values.